Kinetics and mechanism of vacuum isothermal reduction of magnesia by aluminium. (2nd July 2016) - Fu, D. X.; Wang, Y. W.; Peng, J. P.; Di, Y. Z.; Tao, S. H.; Feng, N. X.
Abstract : The kinetics and mechanism of vacuum isothermal reduction of calcined magnesite by Al were studied in the present paper. The results showed that the aluminothermic reduction process was divided into two stages. The apparent activation energy values of the two stages were determined to be 144.4 and 235.3 kJ mol −1, respectively. The phase MgAl2 O4 was formed in the first stage. In the second stage, the intermediate phase Mg0.4 Al2.4 O4 was formed and the phase Al2 O3 was obtained from the further reduction of Mg0.4 Al2.4 O4 . The diffusion of molten aluminium is the rate-determining step of the reduction process. The out diffusion of magnesium vapour has some effect on the reduction ratio at the briquetting pressure between 60 and 120 MPa, but it is not the major rate-limiting step. Dans cet article, on a étudié la cinétique et le mécanisme de réduction isotherme sous vacuum de la magnésite calcinée par l'Al. Les résultats ont montré que le procédé de réduction aluminothermique était divisé en deux étapes. On a déterminé les valeurs d'énergie d'activation apparente des deux étapes à 144.4 et 235.3 kJ/mol, respectivement. La phase de MgAl2 O4 était formée dans la première étape. La phase intermédiaire de Mg0.4 Al2.4 O4 était formée dans la seconde étape et l'on a ensuite obtenu la phase d'Al2 O3 par réduction additionnelle du Mg0.4 Al2.4 O4 . La diffusion de l'aluminium fondu est l'étape cinétiquement déterminante du procédé de réduction. La diffusion vers l'extérieur de la vapeur de magnésium a un certain effet sur le taux de réduction à la pression de briquetage entre 60 et 120 MPa, mais il ne s'agit pas de l'étape majeure cinétiquement limitante.